Spiritual Care in Nursing Practice in Veteran Health Care. (May 2019) - Burkhart, Lisa; Bretschneider, Anna; Gerc, Sharon; Desmond, Mary E.
Spiritual care is important in nursing practice, and spiritual well-being and spiritual care are associated with better health. Military veterans, a unique patient population, want spiritual care to cope with chronic conditions. It is unclear whether spiritual care is provided in veteran health care in the United States. This study used a qualitative descriptive method, guided by the Spiritual Care in Nursing Practice (SCNiP) theory, to describe spiritual care in nursing practice and facilitators/barriers in veteran health care. Individual interviews were conducted with 39 registered nurses (RNs) at a U.S. veteran health system. Findings were consistent with the SCNiP theory but revealed additional categorical attributes and processes as it applied to veteran health care. Facilitators that promoted spiritual care include nurse professionalism, collegial support, and available spiritual resources. Barriers included lack of time, task-oriented culture, unclear knowledge of accessing resources, and unclear organization policy in providing spiritual care. Findings further refined the theory.